Evaluation of the Daily Labor Budget and Calculation of Additional Labor Needs at Hotel XYZ in Makassar - Muhammad Nur abdi; Firmansyah; Astia Lanriupa Natsirm; Muhammad Iqram (International Journal of Business and Quality Research, 2026)
Fluctuations in occupancy rates and the high frequency of special events in the hospitality industry require management to be adaptive in controlling variable operating costs, particularly the budget for casual/daily workers. This study aims to evaluate the effectiveness of implementing activity-based budgeting and flexible budgeting in meeting the need for additional staff at Hotel XYZ in Makassar. Using a quantitative descriptive approach with a case study method, this study analyzes actual budget expenditure data and the number of operational personnel during the transition period of November and December 2025. The results show that the implementation of flexible budgeting at Hotel XYZ in Makassar was highly responsive in addressing peak season demands. There was an 81.48% increase in the number of casual workers (from 27 to 49 personnel), accompanied by an 80.35% increase in budget allocation (from Rp90,217,130 to Rp162,711,180). The Food & Beverage (Kitchen & Banquet) division and the Security department were identified as the primary cost drivers, absorbing the largest portion of the budget to maintain the hotel’s service and security standards. This study concludes that this dynamic budget adjustment is capable of optimizing the hotel’s operational efficiency. Management is recommended to implement strict key performance indicators (KPIs) for casual workers and conduct cross-training to prevent the risk of rising variable costs that could erode the company’s net profitability.